Autologous Bone-Marrow-Derived-Mononuclear-Cells-Enriched Fat Transplantation in Breast Augmentation: Evaluation of Clinical Outcomes and Aesthetic Results in a 30-Year-Old Female - Dmitry Bulgin; Erik Vrabic; Enes Hodzic (Case Reports in Surgery)
Autologous fat transfer (lipofilling) is becoming an invaluable tool for breast augmentation as well as for breast reconstruction. Autologous lipofilling has several advantages, including biocompatibility, versatility, natural appearance, and low donor site morbidity. The main limitation is unpredictable fat graft resorption, which ranges from 25% to 80%, probably as a result of ischaemia and lack of neoangiogenesis. To obviate these disadvantages, several studies have searched for new ways of increasing the viability of the transplanted fat tissue. One promising approach is to enrich the fat graft with autologous bone-marrow-derived mononuclear cells (BMMNCs) before transplantation. BMMNCs produce many angiogenic and antiapoptotic growth factors, and their secretion is significantly enhanced by hypoxia. All of these mechanisms of actions could be beneficial for the stimulation of angiogenesis in ischemic tissues by BMMNCs administration. In our aesthetic surgery practice, we use fat transplantation enriched with BMMNCs, which caused a significant improvement in survival of fat grafts, compared with that of traditional lipofilling. Our experience with freshly isolated autologous fat enriched with BMMNCs for breast augmentation procedures is presented. The concept of this surgical and tissue handling technique is based on ability of BMMNCs to stimulate blood vessel growth.